Executive Function, Language, and the Toddler’s Discovery of Representational Drawing - Panesi, Sabrina; Morra, Sergio (Frontiers in Psychology, 2021)
Working memory capacity and executive functions play important roles in the early development of drawing and language, but we lack models that specify the relationships among these representational systems and cognitive functions in toddlers. To respond to this need, the present study investigated the relations between drawing and language in very young children, and the role of working memory capacity, inhibition, and shifting in the association between these two representational systems. The participants were eighty children, 25 to 37 months old. The results revealed that in toddlers (a) all measures of working memory, inhibition, and shifting loaded on a single factor of general executive functioning; (b) language and drawing are two distinct, but substantially correlated, representational systems; and (c) the development of executive function has a strong impact on language development, which in turn influences the development of drawing.